Analisa Market Performance Transportasi Online di Kota Batam: Studi Kasus Gojek, Grab, dan Maxim - Nurjanah, Listia; Winata, Wendy; Fasha, Andina (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the market performance of online transportation in Batam city. The independent variables in this study are brand equity, marketing innovation, and customer relationship management. Sustainable competitive advantage as a mediating variable, and market performance as the dependent variable. Respondents used are the people of Batam city who have used online transportation services. 256 respondents were obtained by distributing questionnaires online, the results were tested on the Smart PLS application. After the data is tested, it is found that the variables of brand equity and marketing innovation have a significant effect on the market performance of online transportation mediated by sustainable competitive advantage. However, there are customer relationship management variables that have no significant effect on online transportation market performance mediated by sustainable competitive advantage.